The clinical evaluation of the effectiveness of various minimally invasive methods in the treatment of central serous chorioretinopathy (Ukrainian Journal of Ophthalmology, 2025)
Aim: clinical evaluation of the effectiveness of various lasers in treating acute and chronic central serous chorioretinopathy.Methods. The study involved 50 patients (53 eyes) with central serous chorioretinopathy (CSCR): 32 (60.4%) with the acute form and 18 (39.6%) with the chronic form. Patients were divided into three groups based on treatment and the leakage point's (LP) location. Group 1; 19 patients (19 eyes) received focal laser coagulation. Group 2 included 24 patients (24 eyes) who underwent subthreshold micropulse laser treatment (SMLT) for retinal neuroepithelial detachment. Group 3; 7 patients (10 eyes) with chronic disease underwent focal coagulation combined with SMLT, with LP confirmed via fluorescein angiography (FA). The observation lasted 6 months.Results. At the 4-week follow-up, Group 1's best corrected visual acuity (BCVA) improved by 60.2% to 0.75±0.01, with central retinal thickness (CRT) decreasing by 72.8% to 257.2±13.1 µm (p
Keywords: central serous chorioretinopathy; leakage point; subthreshold micropulse laser therapy; optical coherence tomography; fluorescent angiography